Edukasi Dampak NAPZA Dalam Mewujudkan Generasi Taat Hukum, Sehat Dan Bermartabat - M. Firyal Azhar; Dewi Robiatun Muharomah; Siti Nurohmah; Pebi Amanda Rahmawati; Hafizh Nurkholish; Rizky Firmansyah; M. Faizal Al-Aziz; Fitriyani Fitriyani; Maya Rahayu; Nurisa Ainulhaq; Vina Karina Putri (Pusat Riset dan Inovasi Nasional, 2023)
Drug abuse (Narcotics, Psychotropics and Addictive Substances) is like an iceberg that never reaches the root of the problem. It is as if this case was not handled properly because cases are always discovered from year to year. In fact, efforts have been made by related elements to combat this case, assisted by several elements who have a role in prevention. However, the results of the efforts of the government and related parties will never be seen if they are not supported by community efforts. Therefore, the Bina Bangsa University student work study team (KKM) initiated community service activities in the form of education about the negative impacts of drug use on teenagers. It is hoped that after this activity, teenagers' knowledge of NAPZA will increase. Not only does knowledge increase but awareness of the effects of drug use deters teenagers and makes them reluctant to approach these prohibited substances. From the results of the activities, it can be seen that there has been an increase in the knowledge of teenagers who took part in counseling activities. It is hoped that after increasing knowledge, these teenagers will become anti-drug campaign agents in the community.